The Stockholm spinal cord injury study: 1. Medical problems in a regional SCI population - Levi, R; Hultling, C; Nash, M S; Seiger, A (Paraplegia, 1995)
Out of a regional traumatic spinal cord injury population consisting of 379 individuals, 353 (93.1%) participated in the present study. Subjects were individually interviewed using semi-structured protocols. In addition, previous medical records were available for over 96% of subjects, and were used in all these cases to minimise recall bias. Cause of injury, prevalence of present medical symptoms and occurrence of medical complications in the post-acute, post-discharge phase were recorded. Neurological classification was verified by physical examination according to ASIA/IMSOP standards. Many subjects had experienced complications since discharge from initial hospitalisation, especially urinary tract infections, decubitus ulcers, urolithiasis, and neurological deterioration. Prevalence of medical symptoms was also high. More than 41% of subjects with spastic paralysis reported excessive spasticity to be associated with additional functional impairment and/or pain. Almost two-thirds of subjects reported significant pain, with a predominance of neurogenic-type pain. Bladder and bowel dysfunction were each rated by nearly 41% of subjects as a moderate to severe life problem. As expected, sexual dysfunction was also commonly reported. Prevalence of reported symptoms by general systems review was high, particularly fatigue, constipation, ankle oedema, joint and muscle problems, and disturbed sleep. However, lack of adequate normative data precludes comparison with the general population. The frequent occurrence of reported medical problems and complications support advocacy of comprehensive, life-long care for SCI patients. The commonly reported problems of neurogenic pain and neurological deterioration, in particular, require more attention, as these symptoms are not seldom ominous, either by virtue of their impact on quality of life, or because of underlying pathology.